Charge displacement in bacteriorhodopsin during the forward and reverse bR-K phototransition. - Groma, G I (1995)
Dried oriented purple membrane samples of Halobacterium salinarium were excited by 150 fs laser pulses of 620 nm with a 7 kHz repetition rate. An unusual complex picosecond electric response signal consisting of a positive and a negative peak was detected by a sampling oscilloscope. The ratio of the two peaks was changed by 1) reducing the repetition rate, 2) varying the intensity of the excitation beam, and 3) applying background illumination by light of 647 nm or 511 nm. All of these features can be explained by the simultaneous excitation of the bacteriorhodopsin ground form and the K intermediate. The latter was populated by the (quasi)continuous excitation attributable to its prolonged lifetime in a dehydrated state. Least-square analysis resulted in a 5 ps upper and 2.5 ps lower limit for the time constant of the charge displacement process, corresponding to the forward reaction. That is in good agreement with the formation time of K. The charge separation driven by the reverse phototransition was faster, having a time constant of a 3.5 ps upper limit. The difference in the rates indicates the existence of different routes for the forward and the reverse photoreactions.